FACTORS THAT INFLUENCE THE DECISION ON THE PLACE OF SALE OF COFFEE IN NEGERI SINDANG VILLAGE, SOSOH BUAY RAYAP DISTRICT, OGAN KOMERING ULU REGENCY - Sufi Narinna Sari (Universitas Galuh, 2025)
limitations in determining the most profitable marketing channels. This study aims to analyze the factors that influence farmers' decisions in choosing a place to sell coffee, especially to middlemen, in Sindang State Village, Sosoh Buay Terap District, Ogan Komering Ulu Regency. The method used was a survey with a quantitative approach, involving 30 coffee farmers selected through stratified random sampling techniques. The analysis was performed using binary logistics regression with the help of SPSS software. The results of the study show that six variables have a significant effect on the decision of coffee sales places, namely: selling price, mileage, availability of capital, quality of coffee beans, access to price information, and buyer service. Among these variables, economic factors such as selling price (p = 0.025) and capital (p = 0.038), as well as access to price information (p = 0.044) are the main determinants in farmers' decision-making. Meanwhile, the variables of service and distance also strengthened the decision, especially due to the factor of convenience and social relations with middlemen. These findings reflect that although farmers are aware of other sales alternatives, the preference for middlemen remains strong due to practical and relational economic considerations. Keywords: coffee farmers, place of sale, middlemen, logistical regression, economic decisions